Zwitterionic polycondensation fulvic acid corrosion inhibitor and preparation method thereof

Through the polycondensation reaction of chlorosulfuric acid and bis(2-chloroethyl)amine hydrochloride, zwitterionic polycondensation chlorosulfuric acid corrosion inhibitor is formed, which solves the problem that the chlorosulfuric acid modification in the prior art has failed to change the skeleton structure and molecular weight. The problem of this problem has achieved stronger adsorption force and corrosion inhibition effect, expanded the scope of application, and achieved efficient utilization of weathered coal resources.

CN119285930AActive Publication Date: 2025-01-10SUZHOU XIBON SILICONE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411398506.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing chlorophoric acid modification strategy has failed to effectively change the product framework structure, resulting in a significant increase in the molecular weight of the product, limited application scope, and the utilization in the industrial field has not yet achieved performance improvement or functional impartment.

Method used

Through the polycondensation reaction of chlorosulfuric acid and bis(2-chloroethyl)amine hydrochloride, zwitterionic polycondensation chlorosulfuric acid corrosion inhibitor is formed, its skeleton structure is changed, molecular weight is increased, and cationic functional groups are introduced. The preparation method is gentle, Low energy consumption, suitable for water as a medium.

Benefits of technology

It significantly improves the adsorption force and corrosion inhibition effect of corrosion inhibitor, expands its application scope, and realizes the high-value utilization of low-value weathered coal resources, which is in line with the principle of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285930A_ABST
    Figure CN119285930A_ABST
Patent Text Reader

Abstract

The invention discloses a zwitter-ion polycondensation fulvic acid corrosion inhibitor and a preparation method thereof, the corrosion inhibitor takes fulvic acid as a basic polycondensation unit, phenolic hydroxyl groups on a framework of the fulvic acid and bis (2-chloroethyl) amine hydrochloride are subjected to polycondensation reaction to obtain the zwitter-ion polycondensation fulvic acid corrosion inhibitor, and each structural unit contains a fulvic acid framework and a bis (2-ethyl) amine hydrochloride group. Carboxyl in a fulvic acid skeleton shows electronegativity, and a bis (2-ethyl) amine hydrochloride group shows electropositivity. The preparation method has the characteristics of mild reaction conditions, low energy consumption level and capabilities of changing the framework structure of fulvic acid, improving the molecular weight of the product and endowing the product with cationic functional groups. The zwitterionic polycondensation fulvic acid obtained by the preparation method has the function of inhibiting metal corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fine chemical additives, and particularly relates to a zwitterionic polycondensation fulvic acid corrosion inhibitor and a preparation method thereof. Background Art

[0002] Metal corrosion will not only shorten the service life of equipment and bring serious economic losses; at the same time, microscopic corrosion phenomena that cannot be monitored in real time will also lead to a decline in material performance, posing a hidden danger to production safety. Adding corrosion inhibitors to corrosive media is an efficient, simple and economical measure to inhibit the corrosion of metal materials and extend their service life. According to the development ideas of existing corrosion inhibitors, the structure of corrosion inhibitors usually contains heteroatoms (such as N, S, O, P, etc.) and unsaturated bonds (such as double bonds, triple bonds, aromatic rings, etc.). These special groups provide active sites for the adsorption of corrosion inhibitors on the metal surface, which is the key to ensuring corrosion inhibition performance. In addition, compared with traditional small molecule corrosion inhibitors, polymer corrosion inhibitors have the advantages of more adsorption sites and stronger adsorption capacity, which is a new trend in the development of corrosion inhibitors in recent years.

[0003] Fulvic acid is a natural compound with abundant reserves, which mainly comes from weathered coal, sludge, etc. Weathered coal resources in particular have very high reserves in my country, but due to its low calorific value and high water content, it has not been effectively utilized. The long-term dumping of weathered coal not only causes serious waste of resources, but also the humus inside it seeps into groundwater, which also causes organic carbon water pollution.

[0004] At present, fulvic acid is mainly used as agricultural fertilizer, which has beneficial effects such as water retention, promoting plant growth, and improving soil. However, the consumption of fulvic acid in the agricultural field is extremely limited, and new ways to utilize fulvic acid are urgently needed. In the industrial field, fulvic acid is currently modified through some reactions such as sulfonation and nitration, and the modified product is then utilized. However, these modification strategies only achieve changes in some active groups in the fulvic acid structure, and do not fundamentally achieve changes in the product skeleton structure, and cannot achieve a significant improvement in product performance or give the product new functions. Therefore, the scope of application of the product is still very limited.

[0005] In summary, compared with the present application, the defects in the fulvic acid modification process are: the change of the product skeleton structure is not achieved, and the product molecular weight is not significantly improved, resulting in a very limited application range of the product. Summary of the invention

[0006] In order to overcome the above problems in the prior art, the purpose of the present invention is to provide a zwitterionic polycondensation fulvic acid corrosion inhibitor and a preparation method thereof, which has the characteristics of mild reaction conditions, low energy consumption, changing the fulvic acid skeleton structure, increasing the product molecular weight, and giving the product cationic functional groups. The zwitterionic polycondensation fulvic acid obtained by this preparation method has the function of inhibiting metal corrosion.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A zwitterionic polycondensation fulvic acid corrosion inhibitor, which is based on a polycondensation unit of fulvic acid, obtained by a polycondensation reaction between the phenolic hydroxyl group on its skeleton and bis(2-chloroethyl)amine hydrochloride, wherein each structural unit contains a fulvic acid skeleton and a bis(2-ethyl)amine hydrochloride group. The carboxyl group in the fulvic acid skeleton exhibits negative charge, and the bis(2-ethyl)amine hydrochloride group exhibits positive charge.

[0009] A method for preparing a zwitterionic polycondensation fulvic acid corrosion inhibitor, the preparation of the corrosion inhibitor comprising the following specific steps:

[0010] Step 1: Dissolve fulvic acid and bis(2-chloroethyl)amine hydrochloride in water respectively;

[0011] Step 2: Add alkali to the solution of step 1 to adjust the pH to 8-10;

[0012] Step 3: stirring the reaction system with a pH of 8 to 10 at 25 to 35° C., monitoring the pH change of the system during the reaction, and using a base to always maintain the pH at 8 to 10 to obtain a crude product;

[0013] Step 4: After the reaction is completed, the crude product obtained in step 3 is dialyzed in water;

[0014] Step 5: Dry the dialysate to obtain the product, i.e., zwitterionic polycondensation fulvic acid corrosion inhibitor.

[0015] The mass ratio of fulvic acid to bis(2-chloroethyl)amine hydrochloride in step 1 is 1:0.2-1:0.01. Since there are multiple phenolic hydroxyl groups in the structure of fulvic acid, if too much bis(2-chloroethyl)amine hydrochloride is added, a significant cross-linking reaction will occur, resulting in the product being insoluble and unable to be used.

[0016] In step 2, the alkali is any one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, or a combination of two thereof.

[0017] The role and purpose of maintaining the pH at 8-10 in step 3 is that the reaction base is a catalyst, and as the reaction proceeds, hydrochloric acid will be produced, consuming the base, and the reaction will stop if it cannot be catalyzed, so the system must be kept in an alkaline environment.

[0018] The molecular weight cut-off of the dialysis technique in step 4 is 100-1000 g / mol, which is used to remove and recover reactants that have not participated in the reaction.

[0019] The zwitterionic polycondensation fulvic acid corrosion inhibitor is used for inhibiting metal corrosion.

[0020] Beneficial effects of the present invention:

[0021] ① The corrosion inhibitor is prepared using the natural product fulvic acid. The chain extension and polycondensation is achieved through the substitution reaction of the phenolic hydroxyl group in its structure with the halogen in the structure of the dihalogenated compound, thereby increasing its molecular weight. At the same time, cationic groups are introduced to promote adsorption, thereby significantly improving its corrosion inhibition effect compared to the use of fulvic acid alone.

[0022] ② The synthetic technology provided by the invention has mild conditions, does not require high temperature and high pressure operation, and the reaction medium is water, which is green and environmentally friendly and conforms to the development concept of green chemistry. The raw material fulvic acid comes from low-value-added weathered coal, and the invention technology can realize the high-value utilization of low-value resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the synthesis reaction of zwitterionic polycondensation fulvic acid corrosion inhibitor.

[0024] Figure 2 These are the SEM-EDS test results of fulvic acid and zwitterionic polycondensation fulvic acid.

[0025] Figure 3 Nyquist impedance diagram of Q235 carbon steel in 1M HCl solution containing different concentrations of corrosion inhibitor.

[0026] Figure 4 Tafel polarization curves of Q235 carbon steel in 1M HCl solution containing different concentrations of corrosion inhibitors. DETAILED DESCRIPTION

[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0028] Example 1

[0029] This embodiment provides a zwitterionic polycondensation fulvic acid corrosion inhibitor, which is prepared by the following method:

[0030] (1) Dissolve 100 g of fulvic acid and 10 g of bis(2-chloroethyl)amine hydrochloride in water respectively.

[0031] (2) Add NaOH to adjust the pH of the system to 8-10.

[0032] (3) The reaction system was moved to 25-35°C and stirred for 8 hours. The pH of the system was monitored during the reaction and maintained at 8-10 using NaOH.

[0033] (4) After the reaction is completed, dialyze using a dialysis bag with a molecular weight cutoff of 100. After the dialysate is dried, the corrosion inhibitor is obtained.

[0034] raw material:

[0035] Fulvic acid is extracted from weathered coal;

[0036] Potassium hydroxide and sodium hydroxide were purchased from Tianjin Komiou Chemical Reagent Co., Ltd.;

[0037] Potassium carbonate, sodium carbonate, and bis(2-chloroethyl)amine hydrochloride were purchased from Adamas reagent.

[0038] Example 2

[0039] This embodiment provides a zwitterionic polycondensation fulvic acid corrosion inhibitor, which is prepared by the following method:

[0040] (1) Dissolve 100 g of fulvic acid and 20 g of bis(2-chloroethyl)amine hydrochloride in water respectively.

[0041] (2) Add KOH to adjust the pH of the system to 8-10.

[0042] (3) The reaction system was moved to 25-35°C and stirred for 8 hours. The pH of the system was monitored during the reaction and maintained at 8-10 using KOH.

[0043] (4) After the reaction is completed, dialyze using a dialysis bag with a molecular weight cutoff of 1000. After the dialysate is dried, a corrosion inhibitor is obtained.

[0044] Example 3

[0045] This embodiment provides a zwitterionic polycondensation fulvic acid corrosion inhibitor, which is prepared by the following method:

[0046] (1) Dissolve 100 g of fulvic acid and 10 g of bis(2-chloroethyl)amine hydrochloride in water respectively.

[0047] (2) Add Na2CO3 to adjust the pH of the system to 8-10.

[0048] (3) The reaction system was moved to 25-35°C and stirred for 8 hours. The pH of the system was monitored during the reaction and maintained at 8-10 using Na2CO3.

[0049] (4) After the reaction is completed, dialyze using a dialysis bag with a molecular weight cutoff of 100. After the dialysate is dried, the corrosion inhibitor is obtained.

[0050] Example 4

[0051] This embodiment provides a zwitterionic polycondensation fulvic acid corrosion inhibitor, which is prepared by the following method:

[0052] (1) Dissolve 100 g of fulvic acid and 1 g of bis(2-chloroethyl)amine hydrochloride in water respectively.

[0053] (2) Add a mixed alkali of NaOH and Na2CO3 to adjust the pH of the system to 8-10.

[0054] (3) The reaction system was moved to 25-35°C and stirred for 8 hours. During the reaction, the pH of the system was monitored and maintained at 8-10 using a mixed base of NaOH and Na2CO3.

[0055] (4) After the reaction is completed, dialyze using a dialysis bag with a molecular weight cutoff of 100. After the dialysate is dried, the corrosion inhibitor is obtained.

[0056] Comparative Example 1

[0057] The only difference from Example 1 is that bis(2-chloroethyl)amine hydrochloride is not added in this comparative example, and the remaining raw materials and preparation method are the same as those in Example 1.

[0058] Comparative Example 2

[0059] The only difference from Example 1 is that fulvic acid is not added in this comparative example, the pH is adjusted to neutral after the reaction is completed, and dialysis treatment is not performed. The remaining raw materials and preparation method are the same as those in Example 1.

[0060] like Figure 1 As shown, the zwitterionic polycondensation fulvic acid corrosion inhibitor proposed in the invention is based on fulvic acid as the polycondensation unit, and is obtained by the polycondensation reaction of the phenolic hydroxyl group on its skeleton with bis(2-chloroethyl)amine hydrochloride. The hydrochloric acid produced by the reaction is consumed by the catalyst base in the system, so the alkaline environment should be maintained during the reaction. Each structural unit in the product structure contains a fulvic acid skeleton and a bis(2-ethyl)amine hydrochloride group. The carboxyl group in the fulvic acid skeleton exhibits negative charge, and the bis(2-ethyl)amine hydrochloride group exhibits positive charge.

[0061] Structural characterization

[0062] The SEM-EDS spectra of fulvic acid and zwitterionic polycondensation fulvic acid corrosion inhibitor were tested on a S8100 scanning electron microscope equipped with an energy spectrum unit.

[0063] The contents of C, H, N and S in fulvic acid and zwitterionic condensation fulvic acid were determined using a German Elementar Unicube organic element analyzer (EA).

[0064] The elemental composition of fulvic acid raw material and zwitterionic polycondensation fulvic acid corrosion inhibitor was analyzed by two techniques. The results are shown in Table 1, Table 2 and Figure 2 As shown. Both Table 1 and Table 2 show that, compared with the fulvic acid raw material, the content of N element in the zwitterionic polycondensation fulvic acid is significantly increased. Considering that the unreacted bis(2-chloroethyl)amine hydrochloride has been completely removed by dialysis. Therefore, the increase in the content of N element proves that a polycondensation reaction does occur between fulvic acid and bis(2-chloroethyl)amine hydrochloride, and bis(2-chloroethyl)amine hydrochloride is covalently bonded into the structural unit of fulvic acid. The resulting product structure has a carboxyl anion group and a cationic group in the form of a hydrochloride, i.e., it presents a zwitterion. Therefore, the above results show that the zwitterionic polycondensation fulvic acid corrosion inhibitor is successfully prepared by the method proposed by the invention.

[0065] Table 1 Elemental composition of fulvic acid and zwitterionic polycondensation fulvic acid (SEM-EDS test results)

[0066]

[0067] Table 2 Organic element composition of fulvic acid and zwitterionic polycondensation fulvic acid (EA test results)

[0068]

[0069] Performance Testing

[0070] 1) Static weightlessness method to evaluate performance

[0071] The corrosion inhibition performance of the corrosion inhibitor obtained in the examples and comparative examples was tested with reference to SY / T5405-2019. The corroded metal is a standard Q235 steel sheet (5×2.5×0.2cm), the corrosive medium is 1M HCl, the corrosion temperature is 30°C, the corrosion time is 4h, and three parallel samples are hung for each test. The specific operation is as follows: immerse the cleaned standard Q235 steel sheet in 1M HCl containing different concentrations of corrosion inhibitor. After the corrosion is completed, rinse the steel sheet thoroughly with deionized water, dry it, and weigh it accurately. The corrosion inhibition rate is calculated using the following formula.

[0072]

[0073] Where: m0 and m are the weight of the sample before and after corrosion, respectively, v 0 and v are the corrosion rates without and with corrosion inhibitors, respectively, s is the surface area of ​​the corrosion sample, t is the corrosion time, and η is the corrosion inhibition efficiency.

[0074] Table 3 shows the corrosion inhibition efficiency results of Q235 carbon steel after corrosion for 4 hours in 1M HCl solution containing different concentrations of corrosion inhibitor at 30°C. As shown in Table 3, compared with the blank sheet, as the concentration of the corrosion inhibitor increases, the corrosion rate decreases and the corrosion inhibition rate gradually increases. When the addition amount is 200ppm, the corrosion inhibition rates of the product of Example 1 and the product of Comparative Example 1 are 94.59% and 84.57%, respectively. The product of Example 1 is the zwitterionic polycondensation fulvic acid proposed by the present invention. Since the reactant bis(2-chloroethyl)amine hydrochloride is not added in Comparative Example 1, the product is still essentially fulvic acid. Therefore, the comparison between the product of Example 1 and the product of Comparative Example 1 shows that the zwitterionic polycondensation fulvic acid as a corrosion inhibitor can more effectively inhibit the corrosion of Q235 steel in HCl than fulvic acid alone. When Comparative Example 2 is used as a corrosion inhibitor, it promotes the corrosion of Q235 steel in HCl.

[0075] The above comparative experiments show that the zwitterionic polycondensation fulvic acid proposed in the invention has excellent corrosion inhibition performance. This beneficial effect is not only due to the use of fulvic acid and bis(2-chloroethyl)amine hydrochloride, but also because the new species produced by the polycondensation reaction between fulvic acid and bis(2-chloroethyl)amine hydrochloride have a beneficial corrosion inhibition effect.

[0076] Table 3 Corrosion inhibition efficiency of Q235 carbon steel in 1M HCl solution containing different concentrations of corrosion inhibitors at 30℃ for 4 h

[0077]

[0078] 2) Electrochemical method to evaluate performance

[0079] Electrochemical technology was used to verify the conclusions drawn from the above performance comparison. The electrochemical test was carried out on a Shanghai Chenhua CHI660E electrochemical workstation using a three-electrode system, in which Q235 steel sheet was used as the working electrode, saturated calomel electrode was used as the reference electrode, and platinum sheet was used as the counter electrode. The corrosion inhibition performance of Q235 carbon steel in 1M HCl solution containing different concentrations of corrosion inhibitors was tested. The open circuit voltage (OCP) test time was 1200s, and the test frequency range of the electrochemical impedance spectroscopy (EIS) was 100KHz~0.01Hz, with an amplitude of 5mV. The polarization curve was tested within the range of OCP±250mV at a scanning rate of 1mV / s. The corrosion inhibition efficiency was calculated by the following formulas:

[0080]

[0081] Where R ct and R(Ω·cm 2 ) are the charge transfer resistance of blank and inhibitor added, i 0 corr and i corr (μA·cm-2 ) are the corrosion current densities of blank and inhibitor-added samples, respectively.

[0082] Electrochemical impedance spectroscopy Figure 3 The impedance parameters obtained are shown in Table 4.

[0083] Table 4 EIS parameters of Q235 carbon steel in 1M HCl solution containing different concentrations of corrosion inhibitors

[0084]

[0085] The test results show that compared with the blank sample, the diameter of the impedance arc increases after adding the product of Example 1 and the product of Comparative Example 1, and both exhibit a certain corrosion inhibition effect. However, it is obvious that the impedance arc radius of the product of Example 1 is larger. As shown in Table 4, the charge transfer resistance R ct It is greater than the product of comparative example 1. This indicates that the zwitterionic polycondensation fulvic acid has a more excellent corrosion inhibition performance. Figure 4 The test of polarization curves in Table 5 also verifies this result.

[0086] Table 5 Polarization parameters of Q235 carbon steel in 1M HCl solution containing different concentrations of corrosion inhibitors

[0087]

[0088]

[0089] Therefore, although the corrosion inhibition rate values ​​obtained by different technologies have certain deviations due to the different principles of evaluating corrosion inhibition efficiency by electrochemical test method and static weight loss method, the overall rules are consistent. That is, the zwitterionic polycondensation fulvic acid corrosion inhibitor proposed in the invention has better corrosion inhibition performance than fulvic acid. This beneficial effect is caused by the polycondensation reaction, which increases the molecular weight of the corrosion inhibitor and introduces cationic functional groups, which easily form multi-point adsorption with the metal surface, strengthen the adsorption strength and density, and thus have a better protective effect on the metal surface.

Claims

1. A zwitterionic polycondensation fulvic acid corrosion inhibitor, characterized in that: The corrosion inhibitor is based on fulvic acid as the condensation unit, and is obtained by the condensation reaction between the phenolic hydroxyl group on its skeleton and bis(2-chloroethyl)amine hydrochloride. Each structural unit contains a fulvic acid skeleton and a bis(2-ethyl)amine hydrochloride group. The carboxyl group in the fulvic acid skeleton exhibits negative charge, and the bis(2-ethyl)amine hydrochloride group exhibits positive charge.

2. The method for preparing a zwitterionic polycondensation fulvic acid corrosion inhibitor according to claim 1, characterized in that: The preparation of the corrosion inhibitor comprises the following specific steps: Step 1: Dissolve fulvic acid and bis(2-chloroethyl)amine hydrochloride in water respectively; Step 2: Add alkali to the solution of step 1 to adjust the pH to 8-10; Step 3: stirring the reaction system with a pH of 8 to 10 at 25 to 35° C., monitoring the pH change of the system during the reaction, and using a base to always maintain the pH at 8 to 10 to obtain a crude product; Step 4: After the reaction is completed, the crude product obtained in step 3 is dialyzed in water; Step 5: Dry the dialysate to obtain the product, i.e., zwitterionic polycondensation fulvic acid corrosion inhibitor.

3. The method for preparing a zwitterionic polycondensation fulvic acid corrosion inhibitor according to claim 2, characterized in that: In the step 1, the mass ratio of fulvic acid to bis(2-chloroethyl)amine hydrochloride is 1:0.2-1:0.

01.

4. The method for preparing a zwitterionic polycondensation fulvic acid corrosion inhibitor according to claim 2, characterized in that: In step 2, the alkali is any one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, or a combination of two thereof.

5. The method for preparing a zwitterionic polycondensation fulvic acid corrosion inhibitor according to claim 2, characterized in that: The molecular weight cut-off of the dialysis technique in step 4 is 100 to 1000 g / mol.

6. The use of a zwitterionic polycondensation fulvic acid corrosion inhibitor according to any one of claims 1 to 5, characterized in that: The zwitterionic polycondensation fulvic acid corrosion inhibitor is used for inhibiting metal corrosion.

Citation Information

Patent Citations

  • Method for preparing imidazoline quaternary ammonium salt corrosion inhibitor by using soybean oil, and compound metal corrosion inhibitor of imidazoline quaternary ammonium salt corrosion inhibitor

    CN106986828A

  • Mercaptopyrimidine derivative quaternary ammonium salt corrosion inhibitor as well as preparation method and application thereof

    CN114671814A

  • Graphene oxide quaternary ammonium salt type corrosion inhibitor as well as preparation method and application thereof

    CN118271202A